Проблемы и перспективы формирования кластеров с использованием передовых современных технологий на основе кооперации промышленных предприятий и образовательных учреждений - Шамаева, Н.П. (Культура народов Причерноморья, 2013)
В статье рассматриваются механизмы инновационного развития на основе использования
кластеров. Рассматриваются различные схемы взаимодействия в наноиндустрии между
промышленными предприятиями и образовательными учреждениями. Стратегической проблемой для
любого инновационного кластера является обеспечение достаточного объема финансирования. Для
успешного решения этой проблемы необходимо организовать эффективное взаимодействие бизнеса,
представителей науки, преподавателей вузов и государства. У статті розглядаються механізми інноваційного розвитку на основі використання
кластерів. Розглядаються різні схеми взаємодії в наноіндустрії між промисловими підприємствами та
освітніми установами.Стратегічною проблемою для будь-якого інноваційного кластеру є забезпечення
достатнього обсягу фінансування. Для успішного вирішення цієї проблеми необхідно організувати
ефективну взаємодію бізнесу, представників науки, викладачів вузів і держави. The article discusses the mechanisms of innovation-based development of clusters. The different
schemes of cooperation in nanotechnology between industry and educational institutions.The strategic challenge
for any innovation cluster is to ensure sufficient funding.The successful formation and development of the cluster
as a mandatory element requires a fairly high culture of innovation. Currently, there are two opposite situations:
those with pre-existing culture of innovation and development of the system at the local level from the bottom
(these are examples of the United States, Israel, Taiwan, perhaps, India), and the country in which the main problem lies in the creation of this very innovative culture (Russia, Brazil). It should be noted that the systematic
creation of such structures as the innovation cluster, requires solving a number of problems. On one side of the
world there are many examples of successful innovation clusters, and it may seem that it is only necessary to
adapt the experience of other countries to the existing realities. Use a similar approach with extreme caution is
necessary, taking into account the characteristics of the emerging economies.